THE ROLE OF FATHER'S INVOLVEMENT IN PARENTING ON THE SELF-ESTEEM OF LATE ADOLESCENTS EXPERIENCING PARENTAL DIVORCE - Tamara Pradnya Paramitha; Wiwin Hendriani (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research aims to determine whether there is a role of father's involvement in parenting on the self-esteem of adolescents whose parents have divorced and live with their mother. Father's involvement in parenting plays a crucial role in shaping adolescents' self-esteem. Losing one parent due to divorce can hinder the development of self-esteem in adolescents. Father's involvement in child-rearing includes aspects of time, interaction, and attention. This study employs a quantitative approach with a survey method involving late adolescents aged 18-22. The total number of respondents is N=130, using the Perceived Father Involvement Questionnaire and Rosenberg's Self-Esteem Scale. Data analysis is conducted using simple linear regression analysis. The results of the analysis show that father's involvement in parenting has an influence on the self-esteem of late adolescents students. Father involvement contributes as much as 37.7%. Father's involvement in parenting significantly affects the self- esteem of late adolescents.